Pendampingan Penyusunan Peraturan Desa Bagi Anggota Badan Permusyawaratan Desa (BPD) Se Kecamatan Tarumajaya - Kabupaten Bekasi - Riyanto, Slamet; Mamang, Damrah; Intihani, Siti Nur; Fahruddin, Muhammad; Mawardi, Habloel; Arifudin, Arifudin (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat, 2024)
One of the functions of the Village Consultative Body (BPD) as regulated in Permendagri Number 110 of 2016 is to discuss and agree on the Draft Village Regulation with the Village Head. Village Regulations as a policy at the village level that will regulate the behavior of many people must be implemented in a participatory manner involving all components in the village community. Village Regulations are laws and regulations stipulated by the Village Head after being discussed and agreed with the BPD. BPD members in Tarumajaya District, Bekasi Regency, are still experiencing difficulties in drafting Village Regulations. One of the reasons is that the understanding and expertise of BPD members in carrying out their duties in drafting Village Regulations (legal drafting) is still not optimal. The purpose of this PkM activity is to optimize the expertise of BPD members in designing Village Regulations and provide assistance in preparing a participatory Village Regulation Draft in Tarumajaya District, Bekasi Regency, as well as preparing a Village Regulation Draft Template. The method used in PkM is descriptive, with a sociological juridical approach. The activity began by carrying out a legal drafting workshop for BPD members. The next stage of the activity is to collect and review Village Regulation materials that must be prepared immediately to meet the needs of the community. At the peak of this activity is to provide assistance in the preparation of Village Regulations that must be prepared immediately. The results of this PkM activity have been carried out assistance activities for the preparation of the Draft Village Regulations and 2 templates of the Draft Village Regulations have been submitted. In this PkM activity, BPD members also expressed their desire to be accompanied in the preparation of agreements (contract drafting), for this PkM activity has been given assistance on how to prepare a Village Treasury Land Lease Agreement.